Differential expression of TLRs and AKAP3 in cigarette smoked mice testis. (10th May 2019) - Sun, Liping; Shao, Hua; Li, Meng; Zhou, Wenshan
Abstract: Toll‐like receptors (TLRs) are expressed in Sertoli cells and Leydig cells and can initiate testicular innate immune responses. The A‐kinase anchor protein 3 (AKAP3), a family of scaffolding protein, was reported to be expressed only in testis and plays important regulatory roles during spermatogenesis. Our present study aimed to investigate the differential expression of TLRs family and AKAP3 in cigarette smoked Kunming mice testis. To check the effect of cigarette smoke, mice were randomly divided ( n = 5 each) and exposed to cigarette smoke (2 hr/day with 10 cigarettes) for six consecutive days followed by one exposure‐free day. The exposure lasted for zero (control), 1, 3, 5 and 7 months respectively. The IHC results showed that expression of AKAP3 protein is mainly located in sperm cells and the mean density of which was significantly lower than that of control mice. Real‐time PCR results showed that expression of AKAP3 was significantly increased at early CS exposure (1 month) and then returned to normal in subsequent months. TLR2‐7, TLR13, Myd88 and Traf6 mRNA expression are much lower compared to control, especially after 3‐month cigarette smoke exposure, the time of which is almost consistent with sperm cycle. The present study suggests that TLR signal pathway and AKAP3 may play roles in spermatogenesis.